2020
DOI: 10.32479/ijefi.10614
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Government Spending and Economic Growth Revisited

Abstract: This study aims to analyze and verify the relationship between government spending and economic growth. This relationship has been a hot topic for debate among economists, with plenty of research done and being done upon it. This particular study uses panel data from 34 provinces in Indonesia during the 2014-2018 period. During this time, Indonesia's government allocated significant amount of its annual budget towards infrastructure. The estimated econometric test result using the Granger Causality Test did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 16 publications
3
29
0
3
Order By: Relevance
“…BPKP (2021) and Santosa (2022) states that GISA will improve the quality of public services, increase the The results shows that the local budgeting has a significant effect on HDI, IEGI, poverty and per capita GRDP. These results support Fadilah et al, (2018), Mustaqimah et al, (2017), Nurlina, (2015, Patanduk et al, (2019), Putri et al, (2018), andWahyudi, (2020) which states that the local budgeting is primarily for education, health and capital expenditures have a significant impact on welfare. However, these result also in line with Jais (2015) and Rotinsulu et al (2016) study that suggests the local budgeting does not have a significant impact on the unemployment rate.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…BPKP (2021) and Santosa (2022) states that GISA will improve the quality of public services, increase the The results shows that the local budgeting has a significant effect on HDI, IEGI, poverty and per capita GRDP. These results support Fadilah et al, (2018), Mustaqimah et al, (2017), Nurlina, (2015, Patanduk et al, (2019), Putri et al, (2018), andWahyudi, (2020) which states that the local budgeting is primarily for education, health and capital expenditures have a significant impact on welfare. However, these result also in line with Jais (2015) and Rotinsulu et al (2016) study that suggests the local budgeting does not have a significant impact on the unemployment rate.…”
Section: Discussionsupporting
confidence: 85%
“…Local budgeting is used to provide basic needs for society. Previous studies find a positive correlation between governments expenditure and welfare indicators, including HDI (Fadilah et al, 2018;Fahmi & Dalimunthe, 2018;Palayukan, 2019), IEGI (Purwanti & Rahmawati, 2021;Safitri et al, 2021), reducing poverty (Mustaqimah et al, 2017;Pratama & Utama, 2019), decreasing unemployment (Kaharudin et al, 2019;Muslim, 2014), and economic growth (Nurlina, 2015;Patanduk et al, 2019;Putri et al, 2018;Wahyudi, 2020). However, an increase in the local budgeting does not necessarily mean an increase in welfare (Leland, 2005).…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Kuckuck [82] reached contrasting results in his research. Wahyudi [83], meanwhile, only reached conclusions supporting the Keynes Hypothesis. Lastly, Belke and Demir [84] concluded that while Wagner's Law is valid in some countries in the panel, Keynes Hypothesis is valid in other countries.…”
Section: Selected Literaturementioning
confidence: 93%
“…Notably, the ultimate goal of any economic development process is welfare (Wahyudi, 2020). Africa has major development aspirations in the broader context of a global and continental economic development agenda (Economic Development in Africa Report 2016).…”
Section: Developmentmentioning
confidence: 99%